Are Local Governments Liable Under Rule 10b-5? Textualism and Its Limits - Margaret V. Sachs (Washington University Law Quarterly, 1992)
Whether state and local governments can be sued for damages is a question that cuts across subject-area boundaries. This question, which has long confounded courts in the areas of both antitrust and civil rights law, now has arisen in a new area: section 10(b) of the Securities Exchange Act of 19344 and rule 10b-5.
Keywords: Municipal corporations; Textualism (Legal interpretation)